Shifting economic perceptions in South Africa: the impact of migration - Telzak, Samuel C (Department of Sociology, 2016)
For much of South Africa's history, rural areas provided the labor necessary to fuel the furnaces of South Africa's manufacturing and mining sectors. In turn, wage labor in urban areas and mines provided opportunities for black Africans to access the hard currency increasingly necessary for survival. However, since South Africa's transition to democracy, the connection between rural and urban areas has changed dramatically. Through this thesis, I seek to contribute to the nascent literature on the changing relationship between rural and urban areas in South Africa by investigating how economic perceptions - which have been shown to influence voting behavior, resource allocation, mental health outcomes, and the degree of social and political cohesion in a society - differ in both. In particular, I explore how these perceptions are shaped by migration. Migration has framed how generations of black South Africans experienced the South African economic system, either directly, as migrants themselves, or indirectly, as beneficiaries of remittances. This study focuses on a particular migration pathway between "Alfred Nzo" - a district municipality in the rural northeast of the Eastern Cape centered on the town of Mount Frere - and Cape Town. Twenty-six individuals were interviewed, from three different, and socially and economically relevant, migration backgrounds: those who migrated to Cape Town and have remained there ("migrants"), those who migrated to Cape Town but have since returned to Alfred Nzo ("returnees"), and those who have never left Alfred Nzo ("non-migrants").